BEAUTY IS NOT ABOUT BEING WHITE (A Semiotics Analysis of Clean & Clear Advertisement) - Aniek Dwi Lestari; Afdal Makkuraga Putra (IJRDO - Journal of Social Science and Humanities Research, 2020)
Advertisement as a mass media product does not merely offer a product but also contains moral and socio-cultural values ​​that are intended to be communicated to the public through the concepts that are represented. Therefore, this research aimed to figure out and reveal the meaning behind a media text production and how the media texts are represented through a sign system, especially in the “Clean & Clear advertisement version of“1000 Indonesian Tribes, Different Skin Colors". The researcher observed a shift in the representation of beauty. Beauty in this advertisement is not shown in potraits of white skin color, slim, and long hair. It represented in various types of skin color and diverse physical forms of various tribes in Indonesia which represent Indonesia’s diversity. Stuart Hall (Hall, 1997) explains that representation is the practices of social life that produce culture and events called circuit of culture. The circuit of culture describes the relationships or connections between the representations with identity, regulation, consumption, and production. The representation system consists of important components, namely concepts in mind and language. The paradigm in this research is the semiotics analysis using the Roland Barthes model. Barthes concept focuses on two levels, namely the denotative and connotative meaning in order to reveal the myth. The research results showed that Clean & Clear advertisement break the beauty myth that holds that beauty is about being white. It also showed the awareness of plurality by giving an opportunity for dark-skinned and brown-skinned women become the model in adverstisements.